Hospitals : a Design Manual. - Wagenaar, Cor (Design manual (Birkhäuser), 2018)
Hospitals as a building type have undergone a substantial evolution in the past years. Changes in healthcare, the impact of evidence-based medicine and aspects of healthcare economics (such as the clustering of diagnostic procedures in specialized clinics) pose new and different challenges for the designer. Private healthcare facilities herald the paradigm change from the large functional building complex to a design-conscious health institution with luxury hotel features. Health centers more devoted to prevention rather than cure have been another important trend. This publication explains the principles and requirements for the planning of hospitals and other health facilities. An international case study section documents 40 best-practice projects in six categories: general hospitals, children?s hospitals, specialized clinics, outpatient clinics and health centers as well as rehabilitation clinics.